1964
DOI: 10.1152/ajplegacy.1964.207.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endotoxin on capillary permeability to macromolecules

Abstract: The intravenous injection of Escherichia coli endotoxin (3 mg/kg) into dogs caused an increase in lymph flow from the thoracic duct. The lymph concentrations of macromolecules (dextran with mol. wt. of 250,000, albumin-I131, and endogenous proteins) increased and the lymph-to-plasma ratios approached 1. These results indicate that E. coli endotoxin causes an increase in capillary permeability to both the fluid and the macromolecules in plasma. The increase in capillary permeability for albumin-I131 was greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Among the various biological actions of endotoxin, Chien et al (1964) showed an accelerating effect of endotoxin on capillary permeability to macromolecules. Endotoxin was also shown experimentally to cause portal hypertension by constriction of hepatic venules Weil et al 1956;Chien et al 1964). If the above mentioned effect of endotoxin are present in cirrhotic patients, it is possible for endotoxin to cause the retention of ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various biological actions of endotoxin, Chien et al (1964) showed an accelerating effect of endotoxin on capillary permeability to macromolecules. Endotoxin was also shown experimentally to cause portal hypertension by constriction of hepatic venules Weil et al 1956;Chien et al 1964). If the above mentioned effect of endotoxin are present in cirrhotic patients, it is possible for endotoxin to cause the retention of ascites.…”
Section: Discussionmentioning
confidence: 99%
“…20]. Other endogenous substances such as prostaglandins, histamine, lysosomal enzymes, and endotoxin have been implicated in the pathogenesis of increased microvascular permeabil ity and mucosal damage after ischemia and reperfusion [21][22][23][24], These substances are released in the ischemic intestine and enhance the permeability of the intestinal vasculature when infused intra-arterially into normal gut [22,[24][25][26], If these endogenous substances were treated using inhibiting or neutralizing agents, little or no effect was seen [22,[24][25][26], Recently, it has been suggested that the enhanced gen eration of oxygen radicals is intrumental in the develop ment of postischemic mucosal damage.…”
Section: Repcrfusion Injurymentioning
confidence: 99%
“…Respiratory distress developing in patients with gramnegative sepsis has been attributed to increased permeability of lung microvessels (2,32), and E. coli endotoxin increases permeability in canine abdominal viscera (33) and increases the indicator dilution quantity of water in the lungs of anesthetized dogs (34). A commercial Pseudomonas endotoxin preparation causes transient pulmonary arterial hypertension in small doses in calves (35).…”
Section: Response To Pseudomonas Infusionmentioning
confidence: 99%